PENGARUH KONFLIK INTERNAL DAN KONSISTENSI PEMIMPIN TERHADAP KINERJA PEGAWAI KOPERTIS WILAYAH X SUMBAR, RIAU, JAMBI DAN KEPRI - Dedy Julianto, Syahril, (MENARA EKONOMI, 2016)
The title of this research are: Effects of internal conflicts and consistency of leadership toemployee performance at Kopertis X of West Sumatra, Riau, Jambi and Riau Islands.Authors interested in researching this because in daily activities within an organization isinevitable conflicts between superiors and subordinates with between subordinates andsubordinates. This conflict may affect the performance of staff because with this conflictcan also cause people to be out of focus in the work, so as to cause a decline in theperformance of employees working at the institution. Besides, the performance can also beinfluenced by the attitude of a leader in the act because the attitude of a leader that is notconsistent with what he has set or vacillating leaders made subordinate difficult to carryout their work. Leaders are not consistent with the establishment will be able to makeemployee performance will be impaired and these leaders are not appreciated by hissubordinates. For that prompted the leader must be consistent with what has been decidedthat the subordinate can follow, so that the work can proceed smoothly. One of the agencywhich has the above problems is Kopertis X in which allegedly involved frequent internalconflicts among subordinates with superiors and subordinates fellow subordinates even -until employees laid off as a result of the conflict that there is no solution it will be onemployee performance overall. Likewise with leaders allegedly inconsistent with thedecisions and policies that have been taken, so that the performance of employees in theregion Kopertis X is less good. This has been felt by professors who are dealing todaywords like this tomorrow again unlike this exchange, so that lecturers who deal becamepuzzled. Variables used in this research is the internal conflict as the first independentvariable (X1) and Consistency of leadership as the second independent variable (X2) andemployee performance as the dependent variable (Y). Both of these independent variableswill be tested one by one (partial) on the dependent variable how big influence onemployee performance Kopertis region X. This measure is used for quantitative researchmodel using regression analysis multiple as data analysis. In multiple regression analysiswill be able to see how much internal conflict variables affect employee performancesignificantly Kopertis X region as well as the variable consistency of leadership can affectemployee performance Kopertis X region significantly. This is done either partially orcollectively - together.Keywords: Internal Conflict, consistency of leadership and Performance